12x-6=15x+9

Simple and best practice solution for 12x-6=15x+9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12x-6=15x+9 equation:


Simplifying
12x + -6 = 15x + 9

Reorder the terms:
-6 + 12x = 15x + 9

Reorder the terms:
-6 + 12x = 9 + 15x

Solving
-6 + 12x = 9 + 15x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-15x' to each side of the equation.
-6 + 12x + -15x = 9 + 15x + -15x

Combine like terms: 12x + -15x = -3x
-6 + -3x = 9 + 15x + -15x

Combine like terms: 15x + -15x = 0
-6 + -3x = 9 + 0
-6 + -3x = 9

Add '6' to each side of the equation.
-6 + 6 + -3x = 9 + 6

Combine like terms: -6 + 6 = 0
0 + -3x = 9 + 6
-3x = 9 + 6

Combine like terms: 9 + 6 = 15
-3x = 15

Divide each side by '-3'.
x = -5

Simplifying
x = -5

See similar equations:

| 5/7x2/7 | | 2.3333z+3.666=1.3333(z+3.666) | | b-2b=3 | | 2z^6+5z^3-12=0 | | 15+x=30-2x | | 2x-4(4-3x)=x+10 | | 2x-4=4-3x | | 5b+22=2 | | 41-3b=32 | | 9b-4=50 | | 4x^2+-3x+-10= | | 7/3y-5/3=1/3(y-8/3) | | 3x*2-3=0 | | 13=2y-11 | | 5(t+3)=3(2t+1) | | 4v+15=43 | | 8m^2+m=2 | | (8x^2y^2-4x^2y-12xy)/4xy | | (2x-3)/2=(3x-8)/2 | | 2x-17=4+17 | | (2x-3)/2=(3x-8)/3 | | 4r^2-4=172 | | 33=2x+14 | | 4r^2=172 | | 5m^2-24m^2=0 | | 4x^2-15x-4x^3=0 | | 12a+8=20 | | 35+8x=3 | | 35+8x =3 | | 4x^2-xy-5x-5y=0 | | -.05x^2+4.5x-6.5=0 | | -.8x^2+12x+25.8=y |

Equations solver categories